Characterization of decellularized extracellular matrix - Zhao, Jing. (2008)
The objectives of this study were: 1) to develop esophagus-specific procedures for growth factor extraction and electrophoresis; 2) to compare protein compositions of the decellularized esophageal extra cellular matrix (ECM) prepared by various methods.